RESAJANA ZOO – Aplikasi Pengenalan Hewan - Salman Fathul Alfarisyi; Muhammad Refi Darmawan; Jeri Suranta; Ilham Muhammad Haikal; Refriyan Adrianto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Many people do not know the name of the animal if they do not see directly the characteristics of the animal, this is caused by a lack of knowledge about the characteristics of the animal and the lack of references regarding these characteristics even though knowing the characteristics of animals is very important for knowledge if someone is in the forest, at sea and in the air With these problems, an animal identification system is made by knowing the characteristics of the animal